Framework and guidance for implementing patient-reported outcomes in clinical practice: evidence, challenges and opportunities. (August 2016) - Porter, Ian; Gonçalves-Bradley, Daniela; Ricci-Cabello, Ignacio; Gibbons, Chris; Gangannagaripalli, Jaheeda; Fitzpatrick, Ray; Black, Nick; Greenhalgh, Joanne; Valderas, Jose M
Patient-reported outcomes (PROs) are reports of the status of a patient's health condition that come directly from the patient. While PRO measures are a well-developed technology with robust standards in research, their use for informing healthcare decisions is still poorly understood. We review relevant examples of their application in the provision of healthcare and examine the challenges associated with implementing PROs in clinical settings. We evaluate evidence for their use and examine barriers to their uptake, and present an evidence-based framework for the successful implementation of PROs in clinical practice. We discuss current and future developments for the use of PROs in clinical practice, such as individualized measurement and computer-adaptive testing.